2011
DOI: 10.1371/journal.pntd.0001174
|View full text |Cite
|
Sign up to set email alerts
|

Tissue and Stage-Specific Distribution of Wolbachia in Brugia malayi

Abstract: BackgroundMost filarial parasite species contain Wolbachia, obligatory bacterial endosymbionts that are crucial for filarial development and reproduction. They are targets for alternative chemotherapy, but their role in the biology of filarial nematodes is not well understood. Light microscopy provides important information on morphology, localization and potential function of these bacteria. Surprisingly, immunohistology and in situ hybridization techniques have not been widely used to monitor Wolbachia distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(95 citation statements)
references
References 37 publications
4
90
1
Order By: Relevance
“…A recent analysis has shown that Wolbachia of supergroups C and D follow the same pattern of embryonic segregation, starting with mitotic asymmetric segregation to reach a subset of hypodermal cells (Landmann et al, 2010(Landmann et al, , 2012. From there, Wolbachia could invade the ovary and subsequently the germline (Fischer et al, 2011;Landmann et al, 2012). It was suggested that the presence of Wolbachia in the hypodermal cells of their filarial hosts may represent an ancestral somatic tissue-preference, reflecting their mechanism of horizontal transmission (Landmann et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent analysis has shown that Wolbachia of supergroups C and D follow the same pattern of embryonic segregation, starting with mitotic asymmetric segregation to reach a subset of hypodermal cells (Landmann et al, 2010(Landmann et al, , 2012. From there, Wolbachia could invade the ovary and subsequently the germline (Fischer et al, 2011;Landmann et al, 2012). It was suggested that the presence of Wolbachia in the hypodermal cells of their filarial hosts may represent an ancestral somatic tissue-preference, reflecting their mechanism of horizontal transmission (Landmann et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…To date, Wolbachia have not been identified in any other nematode groups (Bordenstein et al, 2003;Duron and Gavotte, 2007), although their presence was suggested in Radopholus similis, a plant-parasitic nematode (Haegeman et al, 2009). Filarial Wolbachia are usually found in the female reproductive apparatus and in the hypodermis (Brattig et al, 2001;Kramer et al, 2003;Landmann et al, 2010;Fischer et al, 2011). The endosymbiont is thought to be mutualistic and ubiquitous in Onchocercidae and to provide essential metabolites to the filariae (Foster et al, 2005;Strübing et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The description of the species 'Candidatus Wolbachia brugii' is based on the studies reported by Fischer et al [34], and Landmann et al [57,58], and Taylor et al [92]. Cell size is 0.5 m up to 1 m. Cells are spherical or have an elongated shape and are surrounded with a double membrane.…”
Section: Description Of 'Candidatus Wolbachia Brugii'mentioning
confidence: 99%
“…After microinjection into Drosophila, Wolbachia infects the stem cell niches in the germ line (16,17), and both Wolbachiaderived and host factors appear to influence tropism and bacterial density during oogenesis (17)(18)(19)(20). Alternatively, somatic tissue may act as a reservoir for Wolbachia infection of the developing oocyte (20)(21)(22)(23). Although pathways of horizontal transmission have been characterized in some species, identification of barriers to vertical transmission of the acquired Wolbachia infection remains elusive.…”
mentioning
confidence: 99%